Implementación de un sistema de riego automatizado empleando dispositivos de control para incrementar la eficiencia en el uso del agua en el barrio Anchilivi en la provincia de Cotopaxi - Cajamarca Chasi, Jeferson Alexander (2022)
This project is based on developing an automated irrigation system for the Anchiliví neighborhood located in the Salcedo canton of the province of Cotopaxi, in the region of Cotopaxi. The system presents the availability to perform two types of irrigation appropriate to the community's needs: drip irrigation activated by processing the humidity and sprinkler irrigation, achieved through a schedule. The irrigation system has a PLC programmer LOGO 12/24 TDE V8.3, which processes the sensors' values and the established times that allow a lower water resource consumption when opening and closing solenoid valves.